2014
DOI: 10.1039/c4sm01354a
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal caterpillars for cargo transportation

Abstract: Tunable transport of tiny objects in fluid systems is demanding in diverse fields of science such as drug delivery, active matter far from equilibrium, and lab-on-a-chip applications. Here, we report the directed motion of colloidal particles and self-assembled colloidal chains in a nematic liquid crystal matrix using electrohydrodynamic convection (EHC) rolls. The asymmetric distortion of the molecular orientation around the particles results -for single particles -in a hopping motion from one EHC roll to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…We direct the structural dipole is antiparallel to the direction of dipole, 0 v < [9]. Theoretically, the amplitude of electrophoretic velocity is predicted to be [9] ( ) [8,9,11,[13][14][15] and in the guiding effect of the director field [8,11,[16][17][18][19], there are no experimental data on how v depends on ε% and σ% , the two crucial properties of the nematic electrolyte. As predicted by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…We direct the structural dipole is antiparallel to the direction of dipole, 0 v < [9]. Theoretically, the amplitude of electrophoretic velocity is predicted to be [9] ( ) [8,9,11,[13][14][15] and in the guiding effect of the director field [8,11,[16][17][18][19], there are no experimental data on how v depends on ε% and σ% , the two crucial properties of the nematic electrolyte. As predicted by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast of the stripe pattern is weak because of the small ∆n. The value is smaller than that of MBBA ∼ 15 µm in the earlier report [22] where the same commercial cells are used. It is also found that the temperature does not change the width so much.…”
Section: Resultsmentioning
confidence: 38%
“…The similar nature is observed for MBBA. [22] However the structure still cannot be maintained in Williams domains. On the other hand, we found that chains with moderate length consisting of ∼ 30 particles or fewer can exhibit a caterpillar-like motion in Williams domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations